THE LEVEL OF KNOWLEDGE, ATTITUDES AND PRACTICES OF MOTHERS ON STUNTING IN NAGARI BUKIK KACIAK LUMPO, PESISIR SELATAN DISTRICT - Saputra, Muhammad Rizki; Tosi Rahmaddian; Irwadi, Irwadi (Nusantara Hasana Journal, 2025)
Stunting is a chronic condition characterized by impaired linear growth in children due to prolonged nutritional deficiencies. It is associated with serious health consequences, including growth failure, developmental delays, and increased risk of non-communicable diseases (NCDs) such as diabetes, cardiovascular disease, and obesity in adulthood. Maternal awareness of nutrition—particularly knowledge, attitudes, and practices (KAP)—is critical in addressing stunting. This cross-sectional observational study was conducted in Nagari Bukik Kaciak Lumpo, Pesisir Selatan Regency, targeting mothers of children who met the inclusion criteria. The data revealed that most respondents were aged 21–60 years, had a high school education, were housewives, and lived in households with two members. The majority of mothers demonstrated good knowledge of stunting, displayed positive attitudes toward its prevention, and engaged in appropriate preventive practices. Conclusion: The study concludes that the majority of mothers in Nagari Bukik Kaciak Lumpo have good levels of knowledge, positive attitudes, and appropriate practices concerning stunting prevention, emphasizing the importance of maternal education in nutritional interventions.